Red Blood Cell Morphologic Abnormalities in Patients Hospitalized for COVID-19 - Marchi, Giacomo; Bozzini, Claudia; Bertolone, Lorenzo; Dima, Francesco; Busti, Fabiana; Castagna, Annalisa; Stranieri, Chiara; Fratta Pasini, Anna Maria; Friso, Simonetta; Lippi, Giuseppe; Girelli, Domenico; Vianello, Alice (Frontiers in Physiology, 2022)
Peripheral blood smear is a simple laboratory tool, which remains of invaluable help for diagnosing primary and secondary abnormalities of blood cells despite advances in automated and molecular techniques. Red blood cells (RBCs) abnormalities are known to occur in many viral infections, typically in the form of mild normo-microcytic anemia. While several hematological alterations at automated complete blood count (including neutrophilia, lymphopenia, and increased red cell distribution width – RDW) have been consistently associated with severity of COVID-19, there is scarce information on RBCs morphological abnormalities, mainly as case-reports or small series of patients, which are hardly comparable due to heterogeneity in sampling times and definition of illness severity. We report here a systematic evaluation of RBCs morphology at peripheral blood smear in COVID-19 patients within the first 72 hours from hospital admission. One hundred and fifteen patients were included, with detailed collection of other clinical variables and follow-up. A certain degree of abnormalities in RBCs morphology was observed in 75 (65%) patients. Heterogenous alterations were noted, with spiculated cells being the more frequent morphology. The group with >10% RBCs abnormalities had more consistent lymphopenia and thrombocytopenia compared to those without abnormalities or <10% RBCs abnormalities (p<0.018, and p<0.021, respectively), thus underpinning a possible association with an overall more sustained immune-inflammatory “stress” hematopoiesis. Follow-up analysis showed a different mortality rate across groups, with the highest rate in those with more frequent RBCs morphological alterations compared to those with <10% or no abnormalities (41.9%, vs 20.5%, vs 12.5%, respectively, p=0.012). Despite the inherent limitations of such simple association, our results point out towards further studies on erythropoiesis alterations in the pathophysiology of COVID-19.